Publication manual of the American Psychological Association : the official guide to APA style (Washington, D.C : American Psychological Association, 2020)
The "Publication Manual" is the style manual of choice for writers, editors, students, and educators. Although it is specifically designed to help writers in the behavioral sciences and social sciences, anyone who writes non-fiction prose can benefit from its guidance. The newly-revised seventh edition has not only been rewritten. It has also been thoroughly rethought and reorganized, making it the most user-friendly "Publication Manual" the APA has ever produced. You will be able to find answers to your questions faster than ever before. When you need advice on how to present information, including text, data, and graphics, for publication in any type of format--such as college and university papers, professional journals, presentations for colleagues, and online publication--you will find the advice you're looking for in the "Publication Manual." It provides invaluable guidance on all aspects of the writing process, from the ethics of authorship to the word choice that best reduces bias in language.
1.Scholarly writing and publishing principles -- 2.Paper elements and format -- 3.Journal article reporting standards -- 4.Writing style and grammar -- 5.Bias-free language guidelines -- 6.Mechanics of style -- 7.Tables and figures -- 8.Works cited in the text -- 9.Reference list -- 10.Reference examples -- 11.Legal references -- 12.Publication process.
Includes bibliographical references and index.
Keywords: PSYCHOLOGY -- AUTHORSHIP